1998
DOI: 10.1007/s005200050161
|View full text |Cite
|
Sign up to set email alerts
|

Anticipatory nausea and vomiting in the era of 5-HT 3 antiemetics

Abstract: Cancer chemotherapy is known to lead to nausea and vomiting in a large proportion of cases. If emesis is severe it can lead in its turn to anticipatory nausea and vomiting (ANV), which cannot be controlled by antiemetic medication. The etiology of ANV and various methods that have been used to counteract the condition are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(31 citation statements)
references
References 42 publications
(10 reference statements)
1
30
0
Order By: Relevance
“…Additionally, the non-intoxicating component of cannabis, CBD, also prevented acute cisplatin-induced vomiting in the shrew. Our results, however, do not address the effects of these agents (or their combination) on phases of nausea and vomiting that are resistant to treatment with serotonin antagonists: a) anticipatory nausea and vomiting experienced during re-exposure to chemotherapy related cues, and b) the delayed phase of nausea and vomiting produced by chemotherapy treatment (Tyc et al 1997;Morrow et al 1998;Fabi et al 2003). It is conceivable that these phases of nausea and vomiting may be more effectively treated by THC or CBD than OND.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Additionally, the non-intoxicating component of cannabis, CBD, also prevented acute cisplatin-induced vomiting in the shrew. Our results, however, do not address the effects of these agents (or their combination) on phases of nausea and vomiting that are resistant to treatment with serotonin antagonists: a) anticipatory nausea and vomiting experienced during re-exposure to chemotherapy related cues, and b) the delayed phase of nausea and vomiting produced by chemotherapy treatment (Tyc et al 1997;Morrow et al 1998;Fabi et al 2003). It is conceivable that these phases of nausea and vomiting may be more effectively treated by THC or CBD than OND.…”
Section: Discussionmentioning
confidence: 59%
“…Indeed, 5-HT 3 antagonists also suppress vomiting in a variety of species, including cats (Rudd et al 2000), ferrets (Ozaki and Sukamoto 1999) and shrews (Torii et al 1991;Ito et al 1995;Andrews et al 1996Andrews et al , 2000Matsuki et al 1997;Darmani 1998). In human clinical trials, although 5-HT 3 antagonists are effective in treating the acute phase of chemotherapy-induced emesis, considerable evidence indicates that the 5-HT 3 antagonists are relatively ineffective in attenuating the delayed phase of chemotherapy induced emesis (Fabi et al 2003) as well as anticipatory nausea and vomiting upon reexposure to the cues associated with treatment (Tyc et al 1997;Morrow et al 1998).…”
Section: Introductionmentioning
confidence: 97%
“…1 Anticipatory vomiting is reported in 20% who experienced vomiting during earlier chemotherapy treatment cycles. 5, 6 Anticipatory, acute and delayed CINV lead to poorer chemotherapy adherence, impaired function, increased anxiety and depression, and diminished quality of life (QOL) among patients. 4, 7–9 In turn, physicians and patients increase utilization of healthcare resources to manage these side effects, substantially increasing the public health burden of cancer and its effective treatment.…”
mentioning
confidence: 99%
“…4, 7–9 In turn, physicians and patients increase utilization of healthcare resources to manage these side effects, substantially increasing the public health burden of cancer and its effective treatment. 4, 7–92–6 The purpose of this chapter is to provide an overview of the patho-psychophysiology of CINV and the recommended guidelines for treatment of CINV.…”
mentioning
confidence: 99%
“…The type of chemotherapy, distinct measurement methodologies [10, 13], severity and duration of previous chemotherapy-associated NV [14, 15, 16, 17, 18, 19], and patient heterogeneity (younger age [7, 11, 15, 20], susceptibility to motion sickness [21], smells and tastes during chemotherapy [10, 22], preexisting anxious state [4, 10, 17, 23, 24], pretreatment expectations of chemotherapy-related nausea [25]) may account for the reported variability. It must be mentioned, however, that no study has reported ANV without the anamnestic finding of posttreatment NV.…”
Section: Introductionmentioning
confidence: 99%